Catolicismos crioulizados: presença centro africana na região do Vale do Paraíba (SP) - Savieto, Mônica Carolina (2011)
Catholicism, in the region of the Vale do Paraíba, throughout the century XIX, got by profound changes. This originality, resulting from the african presence, is remarkable in religious feast of the region even today. This research approach this originality through statuary catholic saints called nó de pinho. The central african presence in the Valley was grimpsed through images of saint nó de pinho, religious festivals, local newspapers, historical demographic data and historic photos. To undestand how groups of enslaved africans taking itself cultural elements which have been imposed the catholicism - translating and creating Áfricas in Brazil, means to focus new subjects historical, new communities and new social dynamics